DIGITALISASI KARAKTER ANTAREJA: EKSPLORASI VISUAL ANIME BERBASIS ELEMEN BUDAYA JAWA: DIGITALIZATION OF ANTAREJA CHARACTER: VISUAL EXPLORATION OF ANIME BASED ON JAVA CULTURAL ELEMENT - Baqal Tazri Virginiawan; Krishna Hutama; Ariani (Fakultas Seni Rupa dan Desain, Universitas Trisakti, 2025)
The proliferation of foreign fiction films and the scarcity of action films set in the Indonesian cultural context have led to a generation of young people becoming complacent and nearly losing their national identity. This issue is particularly significant given the immense enthusiasm for foreign films, especially those with an Anime aesthetic. By digitizing the character of Antareja in an Anime style while preserving Javanese cultural elements, this project aims to integrate Javanese culture into the global lifestyle of today’s youth as part of an effort to preserve Javanese culture. This research will create an Antareja character through comprehensive exploration, using Antareja wayang kulit artifacts as a reference. The character's form will be transformed from its attributes, accessories, and relevant Javanese cultural elements to create an Antareja character in Anime style. A case study approach will be applied to popular modern characters, and the manga Matrix method will be used as a grand theory to design the character's visuals